A case of giant urachal cyst in a neonate - Soichi Nakada; Koji Kumori; Yoko Mizota; Shuichi Ishibashi; Seiji Yano; Showa Aoki; Yoshitsugu Tajima (Elsevier, 2014)
We report a case of giant urachal cyst in a neonate presenting characteristic features on fetal ultrasonography. A 28-year-old woman of 21 weeks gestation was referred to our hospital for evaluation of a cystic mass in the lower portion of the fetal abdomen. On fetal ultrasonography, at 23 weeks gestation, the two umbilical arteries in the base of the umbilical cord became separated from each other due to the fetal cyst. On fetal MRI, at 25 weeks gestation, the cyst was depicted as a unilocular serous cyst, independent of the surrounding organs such as the kidney, gallbladder and intestines. The cyst had no communication with the bladder or umbilical cord. A male infant was delivered at term. Although the infant was thriving and remained asymptomatic, an enhanced CT examination 13 days after birth showed the cyst was still present without any decrease in size. The infant underwent surgery to make a definite diagnosis and to prevent future complications. The cyst was excised without any complication and finally diagnosed as a urachal cyst based on morphological and pathological findings.